Optic Disc Coloboma in children – prevalence, clinical characteristics and associated morbidity. Issue 5 (13th December 2018) - Skriapa Manta, Athanasia; Olsson, Monica; Ek, Ulla; Wickström, Ronny; Teär Fahnehjelm, Kristina
Abstract: Purpose: The aim of the study was to report prevalence, ocular outcome, neurological characteristics, cognitive and behavioural problems in children with optic disc coloboma (ODC). Methods: This was a population‐based, cross‐sectional study of 31 children between 2 and 18 years of age diagnosed with ODC. The children were part of a larger cohort of 184 children with congenital optic disc malformations. Clinical ophthalmological examinations, neurological assessments, behavioural and developmental screening were performed. Results: The prevalence of ODC was 8.9/100 000 children. Of the 31 patients, 18 had unilateral ODC (p = 0.21). The best‐corrected visual acuity (BCVA) in the ODC eye ranged from blindness to 1.3 (median 0.3). BCVA was 0.82 in eyes with an isolated ODC (range 0.4–1.3) and 0.15 (range 0–0.5) in eyes with concurrent macular involvement (p < 0.0001). Nystagmus was observed more often in patients with bilateral ODC (9/13 versus 3/17, p = 0.004). Two patients had retinal detachment. Behavioural/psychological screening was performed in 21 patients with severe deficits identified in six cases. Intellectual disability was present in seven patients. Neurological dysfunction was diagnosed in 8/22 cases. All of the above children had already systemic diagnoses before the ODC diagnosis was made. Conclusions: ODC was the second most common optic disc malformation in this cohort after optic nerve hypoplasia. The children had a wide range of ocular comorbidity. An isolated ODC without macular involvement was not associated with profound vision loss. The ability of screening in the regular child care centres to diagnose extraocular comorbidities was very good and referral to a paediatrician appears redundant in cases of normal development.